Supply Chain Management of Apple Production and Marketing in Kinnaur District of Himachal Pradesh - Abhishek; Raina, Krishan Kumar; Negi, Aparna (International Journal of Economic Plants, 2023)
Present study was conducted to assess the impact of Supply chain Management of Apple Production and study the existing status of Apple production and marketing in Kinnaur district of Himchal Pradesh, India using data for the period 2021–2022. To identify the objectives of the study, a sample of 200 respondents was interviewed through structured interview schedule. The orchard area was 79.26% in Kinnaur, in which irrigated and un-irrigated land was 32.71 and 67.29%. 44% of the sampled respondents were in the category of marginal land holdings, small land holdings were possessed by 46.00%, medium were possessed by 9.00% and large land holdings only 1.00% of sampled household in study area. The various input supply chains identified in apple production in the study area are Channel-I, Channel- II, Channel- III. . Out of all three channels, the channel III is found to be efficient with modified market efficiency of 47.3%. The producer share for consumer’s rupees is 81.81% with net marketing margin was 180 with price spread value of 380. The total cost for production of apple on one hectare of land holdings was observed to be ` 51258 on overall basis. 77.00% of the respondents were aware about the constraints in supply chain apple producers were not so aware about the effective supply chain management and it can be reduced by the efficient supply chain management.